2021
DOI: 10.34172/jlms.2021.36
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Er:YAG Laser and Reduced Time of Acid Etching on Bond Strength of Self-adhesive Resin Cement to MTA and Biodentine

Abstract: Introduction: Considering the recent trend to use mineral trioxide aggregate (MTA) and Biodentine and resin cements, more conservative approaches concurrent with adequate bond strength have always been requested. The present study aimed to evaluate the effect of pretreatment with Er:YAG laser etching versus acid-etching for 5 and 15 seconds on the micro shear bond strength of self-adhesive resin cement (SRC) to MTA and Biodentine. Materials and Methods: Forty-eight samples of each cement (MTA and Biodentine) w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 22 publications
0
2
0
Order By: Relevance
“…Hollow structures and hydrophilic groups (−OH, −COOH) are established on the substrate surface after etching, which could absorb catalytic particles by means of coordinate bonds, thus improving the adhesion. However, most substrates are perishable once exposed to etching solution; as a result, a new surface pretreatment process will be researched for its resistance to deformation after immersing in etching solution. In addition, the CrO 3 /H 2 SO 4 micro-erosion system is used in industrial production, which causes persistent pollution to the environment and is highly carcinogenic to the health of the body, which then limit this technology’s green development. To overcome the issue, the introduction of a modified layer is an ideal choice to be utilized to establish the hydrophilic group for adsorbing catalyst particles on the substrate surface.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Hollow structures and hydrophilic groups (−OH, −COOH) are established on the substrate surface after etching, which could absorb catalytic particles by means of coordinate bonds, thus improving the adhesion. However, most substrates are perishable once exposed to etching solution; as a result, a new surface pretreatment process will be researched for its resistance to deformation after immersing in etching solution. In addition, the CrO 3 /H 2 SO 4 micro-erosion system is used in industrial production, which causes persistent pollution to the environment and is highly carcinogenic to the health of the body, which then limit this technology’s green development. To overcome the issue, the introduction of a modified layer is an ideal choice to be utilized to establish the hydrophilic group for adsorbing catalyst particles on the substrate surface.…”
Section: Introductionmentioning
confidence: 99%
“…However, most substrates are perishable once exposed to etching solution; as a result, a new surface pretreatment process will be researched for its resistance to deformation after immersing in etching solution. In addition, the CrO 3 /H 2 SO 4 micro-erosion system is used in industrial production, which causes persistent pollution to the environment and is highly carcinogenic to the health of the body, which then limit this technology’s green development. To overcome the issue, the introduction of a modified layer is an ideal choice to be utilized to establish the hydrophilic group for adsorbing catalyst particles on the substrate surface. Sun et al, Chang et al, Wang et al, Gui et al, and Huang et al reported that metal particles could be ECP deposited on the substrate surface by a modified, adsorbed, and plated process.…”
Section: Introductionmentioning
confidence: 99%